Essay about how Macunaima helped me to speak about Mathematics Education - Lins, Romulo [UNESP] (Unesp-dept Mathematica, 2011)
As if aesthetics were not content. But as we are faced with some other language (frequently called incorrect), our inclination is to correct it or to want to correct it: not luv, boy! But that's what we hear, not what should be. This essay is, based on aesthetics, a testimony about not being ashamed of its contribution to the field (Mathematics Education) - as a contribution and not 'only' style. The usual parametres for research papers are kept on check.
Keywords: Literature; Essay; Macunaima; Mathematics Education